(untitled) (Research, Society and Development, 2024)
Some of the worst effects associated with the Zika virus infection during gestation include microcephaly, and central nervous system damage. Pregnancy-related physical exercise is recognized to improve both the mother’s and her unborn child’s health. It is widely known that male newborns of late-pregnancy mother infection tend to exhibit more depressive and anxious behaviors as they age. However, nothing is known about how the Zika virus could affect a mother’s behavior in the first few days after giving birth. The objective of this study was to evaluate if 4 weeks of moderate-intensity swimming during pregnancy prevents negative outcomes of prenatal Zika infection in the behavior of the dams. Dams were randomly selected and divided into three groups: Mock (n= 8) - untrained group, intraperitoneally injected with saline; Zika (n = 8) - untrained group, intraperitoneally injected with Zika; and Zika/swim (n = 8) - trained group, intraperitoneally injected with Zika. The swimming sessions were initiated before mating, which occurred between the 5th and 7th day of the 1st week of the swimming training, according to the estrous cycle and lasted until the parturition date. Prenatal Zika virus infection did not change maternal body weight or maternal behavior significantly independently of performing or not physical exercise.